Review of Emergency Medical Services Vulnerability to High Consequence Infectious Disease in the United States - Richey, Thomas W.; Fowler, Raymond L.; Swienton, Ray E.; O'Neal, James Patrick; Harris, Curtis A. (Frontiers in Public Health, 2021)
Purpose: Emergency medical services (EMS) responders are a group of medically skilled professionals who perform a wide range of essential medical services within a community including emergency response, patient transport, and mobile integrated healthcare. The proper functioning of the EMS system is paramount to the well-being of the medical system and public health. The intent of this paper is to review current EMS standards and practice to determine the danger a high consequence infectious disease (HCID) may pose to these healthcare workers and the community. Areas Addressed: Through the review of EMS practice several areas were identified as vulnerabilities to the EMS network. These vulnerabilities consisted of the lack of standardized licensing practice, inconsistent medical direction, and the inability to properly implement the use of personal protective equipment (PPE). The compounding of these vulnerabilities allows for HCIDs to pose a serious threat to EMS personnel with the possibility of devastating and crippling the EMS infrastructure within the US. Discussion: The vulnerabilities identified must be addressed both to protect EMS providers and to enhance the resilience of the US healthcare system. Ways to address the identified vulnerabilities should focus on improving the EMS curriculum and increasing minimum levels of education for first responders. Targeting minimum education and training standards could be the most effect method of reducing the dangers of HCIDs to EMS systems.